2020
DOI: 10.1177/0957650919898983
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of dual-arc blades in a squirrel-cage fan using modified non-dominated sorting genetic algorithm

Abstract: In this study, a dual-arc profile parameterized by four geometric variables was designed to replace the original single-arc profile of a squirrel-cage fan used in a range hood, in order to improve the efficiency of the entire machine and the fan pressure. A modified Non-dominated Sorting Genetic algorithm coupled with a three-dimensional Reynolds-averaged Navier–Stokes computation is applied to search the optimum blade shape. Moreover, a relatively coarse but proven reliable grid model is employed to accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The impeller is the only rotating part of the fan, and its shape greatly influences the internal flow field and performance of the squirrel-cage fan. Yang et al [24] used more complex double-arc blades to replace the commonly used single-arc blades. It was found that compared with single-arc blades with the same inlet and outlet angles, double-arc blades have higher fan pressure and harm efficiency.…”
Section: Geometric Modelmentioning
confidence: 99%
“…The impeller is the only rotating part of the fan, and its shape greatly influences the internal flow field and performance of the squirrel-cage fan. Yang et al [24] used more complex double-arc blades to replace the commonly used single-arc blades. It was found that compared with single-arc blades with the same inlet and outlet angles, double-arc blades have higher fan pressure and harm efficiency.…”
Section: Geometric Modelmentioning
confidence: 99%
“…Hence for the purpose of energy conservation, researchers from both academic and industry communities have devoted numerous efforts to elevate the aerodynamic performance of squirrel cage fans by redesigning or optimizing the impeller blade. [1][2][3] With deeper understanding of the loss mechanisms in the squirrel cage fan, increasing attention is paid to investigation of the stationary components, i.e., the inlet nozzle and the outlet volute. The flow in the stationary components has a large pressure gradient or a non-uniform pattern, and then causes considerable energy los.…”
Section: Introductionmentioning
confidence: 99%
“…Ciocan et al 15 and Marjavaara et al 14 used RSM in conjunction with NSGA-II to optimize the shape of a simplified hydraulic turbine, which improved the hydraulic performance. Therefore, the surrogate model (RSM) and multi-objective evolutionary algorithm (NSGA-II), which have proven their search effectiveness and reliability to obtain the Pareto frontier, 17,18 are applied for the siphon shape optimization analysis. Air compressibility has not been considered during the siphoning formation process in previous research.…”
Section: Introductionmentioning
confidence: 99%
“…Figure18. The distribution of the hydraulic loss coefficient in the different parts of the original and optimized designs.…”
mentioning
confidence: 99%